2018
DOI: 10.1111/jeb.13373
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for the paraphyly of Scolecophidia and its evolutionary implications

Abstract: The phylogenetic relationships between the three main clades of worm snakes remain controversial. This question is, however, crucial to elucidate the origin of the successful snake radiation, as these burrowing and miniaturized wormlike organisms represent the earliest branching clades within the snake tree. The present molecular phylogenetic study, intended to minimize the amount of missing data, provides fully resolved inter-subfamilial relationships among Typhlopidae. It also brings robust evidence that wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 51 publications
0
69
0
1
Order By: Relevance
“…As such, the two distinct scolecophidian clades that currently inhabit the northeastern Mediterranean, i.e., Typhlopidae (genera Letheobia Cope, 1869, andXerotyphlops Hedges, Marion, Lipp, Marin, andVidal, 2014), and Leptotyphlopidae (genus Myriop-holis Hedges, Adalsteinsson, and Branch in Adalsteinsson et al, 2009) cannot be reliably identified in the European fossil record. This is rather frustrating, given that typhlopids and leptotyphlopids are believed to have diverged from each other during the Mesozoic (Adalsteinsson et al, 2009;Miralles et al, 2018). Taking into consideration all these aspects, it is currently impossible to determine whether the new Maramena scolecophidians pertain to any of these genera or even represent a now locally or totally extinct lineage.…”
Section: Diversity Affinities and Palaeobiogeography Of The Maramenmentioning
confidence: 99%
“…As such, the two distinct scolecophidian clades that currently inhabit the northeastern Mediterranean, i.e., Typhlopidae (genera Letheobia Cope, 1869, andXerotyphlops Hedges, Marion, Lipp, Marin, andVidal, 2014), and Leptotyphlopidae (genus Myriop-holis Hedges, Adalsteinsson, and Branch in Adalsteinsson et al, 2009) cannot be reliably identified in the European fossil record. This is rather frustrating, given that typhlopids and leptotyphlopids are believed to have diverged from each other during the Mesozoic (Adalsteinsson et al, 2009;Miralles et al, 2018). Taking into consideration all these aspects, it is currently impossible to determine whether the new Maramena scolecophidians pertain to any of these genera or even represent a now locally or totally extinct lineage.…”
Section: Diversity Affinities and Palaeobiogeography Of The Maramenmentioning
confidence: 99%
“…The infraorder Scolecophidia sensu lato (see Miralles et al. ; Fig. ) consists of five families: Typhlopidae, Gerrhopilidae, Xenotyphlopidae (together constituting the superfamily Typhlopoidea), Anomalepididae, and Leptotyphlopidae (Vidal et al.…”
Section: Introductionmentioning
confidence: 99%
“…; Zheng & Wiens, ; Harrington & Reeder, ; Streicher & Wiens, ; Miralles et al. ). The question of scolecophidian monophyly is therefore putatively resolved (Miralles et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations